Assessment of the Impact of Increased Physical Activity on Body Mass and Adipose Tissue Reduction in Overweight and Obese Children - Marta Nowaczyk; Krystyna Cieślik; Małgorzata Waszak (MDPI AG, 2023)
(1) Background: Within the last 30 years, growing rates of child overweight and obesity have been observed as a very concerning phenomenon in most countries worldwide. The research aim was to assess what effect increased physical activity has on reducing body mass and adipose tissue in children between 10 and 11 years of age as well as to answer the question of whether physical activity could be considered as a factor in preventing child overweight and obesity when maintaining their existing diet and lifestyle. (2) Material and methods: There were 419 sports class primary school pupils in the experimental group who, in addition to four obligatory weekly physical education hours, attended six training hours. The control group comprised 485 children from parallel non-sports classes. In all pupils, height and weight measurements as well as physical fitness measurements were taken twice, at the beginning and end of the school year. Cole's method was used to assess the children's normal body weight. With the help of this method, children with excessive body weight were selected from the entire study group (N = 904), who additionally had skinfolds and adipose tissue measured using the BIA electrical bioimpedance method. The obtained results were interpreted using the variance analysis for repeated measurements and LSD test. (3) Results: The number of children with excessive body mass after 10 months of increased physical activity decreased (in the case of overweight: p = 0.0014, obesity: p = 0.0022), as did their skinfolds (p ≤ 0.001) and body fat (p ≤ 0.001), while their physical fitness considerably improved compared to the control group. (4) Conclusions: The introduction of increased physical activity in the experimental group children when maintaining their existing diet and lifestyle contributed to reducing their obesity and overweight and, at the same time, proved to be an effective factor in the process of decreasing their excessive body mass.